Analyzing the Practicality of the School Capacity Building Training Module to Foster a Child-Friendly School Climate in Elementary Schools - Kholik, Abdul; Suharsiwi; Suradika, Agus (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the practicality of the School Capacity Building training module (SCB-ISRA), which was designed to support the creation of a child-friendly school climate at the elementary level. The research employed a Research and Development (R&D) approach using the ADDIE model through a sequential exploratory design. A limited trial was conducted at a private elementary school in Bogor Regency involving the principal, 29 teachers, 25 students, and five external stakeholders. Data were collected using a practicality assessment instrument covering aspects of attractiveness, readability, ease of use, and usefulness, and were analyzed through descriptive statistics using the Weighted Mean Score (WMS). The findings revealed that the SCB-ISRA module received average scores of 4.26 from teachers, 4.17 from students, and 4.57 from stakeholders, all of which fall within the categories of practical to highly practical. These results indicate that the module is not only feasible for use but also relevant to the real needs of elementary schools.